Afterburning Aspects in an Internal TNT Explosion. Issue 1 (March 2013) - Edri, I.; Feldgun, V.R.; Karinski, Y.S.; Yankelevsky, D.Z.
The afterburning is a complex chemical process which stems from the reaction of the detonation products with the oxygen in the air when appropriate conditions exist. TNT is a very fuel-rich explosive as indicated by the large negative oxygen balance value of −74%. It means that there is not enough oxygen in its initial chemical compound and extra oxygen is needed to make the afterburning energy release possible. This article describes in details the calculation process for evaluating the amount of energy release in a confined TNT explosion. Moreover, partial afterburning energy release is also calculated for cases of oxygen deficiency. Commonly, numerical simulations take into account only the detonation energy in blast pressure analysis and it is responsible for under prediction of blast pressures in a confined explosion. Accounting for the afterburning energy as well considerably improves the predictions and yields pressures that are in good correspondence with measured data. The calculation time however increases by an order of magnitude. An afterburning coefficient was defined as the relation between the total energy released and the detonation energy. This coefficient was found useful for correcting numerical simulation results of TNT confined explosion which take into account only the detonation energy. This correction can be achieved by multiplying the pressure-time history with the afterburning coefficient. In addition, an analytic method, based on thermodynamic rules, was developed for calculating the gas pressure resulted by TNT confined explosion. This unique method takes into account the variation of the total energy released and the heat capacity ratio depending on the ratio between the charge weight divided by the confined air volume. The gas pressure obtained using this method was shown to be in good agreement with experimental results that are published in the literature.